Combination antibiotic therapy in an outbreak of prosthetic endocarditis caused by Staphylococcus epidermidis. - Hammond, G. W. (1978)
The efficacy of combination antibiotics in vivo and in vitro was studied during an outbreak of prosthetic endocarditis caused by Staphylococcus epidermidis in 10 patients. The epidemic curve suggested that patients were infected at the time of their operation, with an interval from that time until diagnosis of 11 days to 20 months. The overall mortality was 50%. Four of six patients treated with gentamicin in combination with a penicillin analogue, a cephalosporin or clindamycin survived without reoperation. One of four patients survived when treated with regimens that did not include gentamicin. In vitro studies showed a median minimum inhibitory concentration for methicillin of 8.0 microgram/mL, compared with 0.1 microgram/mL for cephalothin, clindamycin and gentamicin, and a synergistic bactericidal effect between gentamicin and methicillin, cephalothin or clindamycin. These data suggest that gentamicin is a valuable component of combination antibiotic therapy in prosthetic endocarditis caused by S. epidermidis.